Large‐Scale Screening of Natural Products Transactivating Peroxisome Proliferator‐Activated Receptor α Identifies 9S‐Hydroxy‐10E, 12Z, 15Z‐Octadecatrienoic Acid and Cymarin as Potential Compounds Capable of Increasing Apolipoprotein A‐I Transcription in Human Liver Cells. Issue 11 (1st February 2019) - van der Krieken, Sophie E.; Popeijus, Herman E.; Bendik, Igor; Böhlendorf, Bettina; Konings, Maurice C. J. M.; Tayyeb, Jehad; Mensink, Ronald P.; Plat, Jogchum
Abstract: Increasing apolipoprotein A‐I (apoA‐I), the predominant protein of high‐density lipoprotein (HDL) particles, has favorable effects on atherogenic risk factors. Here, we investigated the effects of peroxisome proliferator‐activated receptor α (PPARα) transactivating compounds on apoA‐I transcription in HepG2 cells. A transient PPARα agonist transactivation assay was used to screen 2500 natural compounds. To analyze the effects on apoA‐I transcription, human hepatocellular liver carcinoma (HepG2) were exposed to 0.1, 1, and 10 μg/mL of the natural PPARα transactivators. ApoA‐I mRNA expression was determined by quantitative polymerase chain reaction. Extensive dose–response experiments were performed using compounds that increased apoA‐I transcription by minimally 20%. Kelch‐like ECH‐associated protein 1 (KEAP) and carnitine palmitoyltransferase 1 alpha ( CPT1α ) expression were used respectively to confirm Bromodomain‐containing protein 4 inhibition or PPARα activation. Twenty‐eight natural compounds increased PPARα transactivation by at least twofold. Despite the increased CPT1α expression seen after the addition of most PPARα activating compounds, CPT1α expression and PPARα transactivation did not correlate. Addition of 0.05 μg/mL 9S‐hydroxy‐10E, 12Z, 15Z‐octadecatrienoic acid (9(S)‐HOTrE) increased apoA‐I mRNA expression by 35%, whereas 10–25 μg/mL of cymarin increased apoA‐I transcription by 37%. However, combining cymarin and 9(S)‐HOTrE did not result in a synergistic effect, in contrast this combination even decreased apoA‐I transcription. ApoA‐I transcription involves multiple regulatory players, and PPARα transactivation alone is not sufficient. A search for natural compounds resembling the molecular structure of 9(S)‐HOTrE or cymarin could aid to find additional components that increase apoA‐I transcription.